Soil organic carbon saturation in cropland-grassland systems: Storage potential and soil quality - Guillaume, Thomas; Makowski, David; Libohova, Zamir; Bragazza, Luca; Sallaku, Fatbardh; Sinaj, Sokrat (Geoderma, 2022)
[Display omitted] •Mineral-associated organic C deficits in croplands and grasslands were estimated.•The relationship between soil C-saturation and soil physical quality was assessed.•Challenges to the C-saturation concept and the SOC:clay ratio were highlighted.•C-saturation in grassland was positively linked to SOC accrual history.•SOC accrual is more beneficial for soil physical quality in croplands. Reliable estimations of soil organic carbon (SOC) deficits in agroecosystems are crucial in evaluating the atmospheric C sequestration potential of agricultural soils and supporting management decisions. Nonetheless, the co-benefit on soil quality resulting from SOC accrual is rarely considered. Here, we assessed SOC saturation and soil physical quality in permanent grasslands (PG) and croplands (CR) by applying the C-saturation concept and the SOC:clay ratio as an indicator of soil physical quality to a set of long-term monitoring sites in western Switzerland. For this goal, we produced a new relationship between the silt + clay (SC) particles and the C stored in the mineral-associated fraction (MAOMC) and we assessed the assumption that grasslands can be used as C-saturated reference sites. The saturation in PG was not coincidental as it depended on the C accrual history. Hence, PG with the lowest MAOMC have not reached their C-saturation level and present a potential SOC storage under optimal management. The MAOMC saturation in CR was low (62 ± 4%) and corresponded to a deficit of −8.8 ± 1.2 mg C g−1 soil as compared to the current level in PG. The saturation was mainly affected by the proportion of temporary grassland in the crop rotation. The relative distribution of C between MAOM (∼80%) and the fine and coarse particulate organic matter (POM) was not affected by land-use types. The MAOMC saturation in this study (MAOMC = 0.372 × SC + 4.23) was similar to that reported in the litterature, but discrepancies appeared when the silt and clay contents were considered separately. SC was by far the main factor explaining MAOMC amount in PG (semi-partial R2: 0.66). In contrast to other studies, the C content of MAOM in PG (43 mg C g−1 SC) was not related to the SC content, suggesting a fixed maximal value in C-saturated soils. Nonetheless, MAOMC saturation may be underestimated as the least saturated PG might still accumulate MAOMC. Finally, the SOC:clay ratio was correlated with MAOMC saturation level in CR, but not in PG suggesting that targeting SOC accrual in CR optimizes the benefits between soil C storage and soil quality.